2020
DOI: 10.5539/gjhs.v12n9p30
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Village Health Volunteers’ Competencies for Tuberculosis Care in Trang Province, Thailand

Abstract: BACKGROUND: Tuberculosis (TB) is a major public health concern resulting in high rates of morbidity and mortality worldwide, particularly in low- and middle-income countries, despite treatment having been available for over 50 years. It remains a crucial health problem in Thailand. This study aimed to develop a program for building tuberculosis (TB) care competencies of village health volunteers (VHVs) and to examine its effects on the outcomes of care for TB patients. METHODS: The competency deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Moreover, Choowong et al. [ 11 ] reported that care service delivery by VHVs in their communities allowed VHVs to make themselves heard and demonstrate their competency to healthcare professionals, which enhanced healthcare professionals’ confidence in working with VHVs [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Choowong et al. [ 11 ] reported that care service delivery by VHVs in their communities allowed VHVs to make themselves heard and demonstrate their competency to healthcare professionals, which enhanced healthcare professionals’ confidence in working with VHVs [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Thailand, as in many low-to-middle-income countries in transition, failure to effectively implement evidence-informed intervention for older adults with chronic diseases represents a key obstacle in the progress of the healthcare system, resulting from the high burden of disease and the extreme shortage of human and material resources [ 8 ]. Thailand also faces major barriers to providing health promotion and optimal care for older adults, especially those in rural areas, due to a lack of access to quality healthcare services, poverty, and low health literacy [ [9] , [10] , [11] ].…”
Section: Introductionmentioning
confidence: 99%